Current Treatments of Prader-Willi Syndrome: A Systematic Review - Zhu, BS, Junli; Kong, MD, Xuejun (North American Journal of Medicine and Science, 2017)
Prader-Willi Syndrome (PWS) is a genetic imprinting disorder mainly caused by the absence of paternally expressed imprinted genes at 15q11.2-q13, maternal uniparental disomy (UPD) and imprinting defect. Typical features include hypotonia in early infancy, subsequent hyperphagia and morbid obesity, developmental delay and intellectual disability. The aims of this systematic review are to summarize the current knowledge of the treatments for PWS based on the clinical studies published from 2000 to 2017. We searched three main databases - PubMed, MEDLINE, and Scopus, and selected 34 out of 1139 articles initially identified for this review. We focused our discussions on the widely-accepted growth hormone (GH) treatment, and emerging investigational treatments oxytocin (OXT), anti-diabetes and anti-obesity drugs. In addition, early detection, early treatment, and combination therapies are proposed to assure a better outcome. [N A J Med Sci. 2017;10(4):156-163. DOI: 10.7156/najms.2017.1004156]